2019
DOI: 10.1001/jamaoncol.2019.1568
|View full text |Cite
|
Sign up to set email alerts
|

Association of Immune Marker Changes With Progression of Monoclonal Gammopathy of Undetermined Significance to Multiple Myeloma

Abstract: Question. Do changes in serum immune markers over time predict progression from monoclonal gammopathy of undetermined significance (MGUS) to multiple myeloma? Findings. Individuals with low-risk/intermediate-risk MGUS can convert to high-risk MGUS and progress to multiple myeloma within years; the same result was found in light-chain MGUS. Evolving monoclonal proteins, serum free light chains, and immunosuppression were associated with progression.Meaning. Our finding that clinical risk categories can change o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 23 publications
(80 reference statements)
2
62
0
Order By: Relevance
“…This is supported by a recent study that investigated serum immune markers in MGUS patients over time [14]. Authors found for the first time a conversion from low-to high-risk MGUS based on changes in monoclonal proteins in up to 70% of patients with high-risk disease before progression [14]. These findings and our current study support repeated risk assessments in patients with asymptomatic plasma cell diseases.…”
Section: To the Editorsupporting
confidence: 90%
See 1 more Smart Citation
“…This is supported by a recent study that investigated serum immune markers in MGUS patients over time [14]. Authors found for the first time a conversion from low-to high-risk MGUS based on changes in monoclonal proteins in up to 70% of patients with high-risk disease before progression [14]. These findings and our current study support repeated risk assessments in patients with asymptomatic plasma cell diseases.…”
Section: To the Editorsupporting
confidence: 90%
“…However, risk of progression is not constant but might actually change during the course of the disease due to clonal evolution. This is supported by a recent study that investigated serum immune markers in MGUS patients over time [14]. Authors found for the first time a conversion from low-to high-risk MGUS based on changes in monoclonal proteins in up to 70% of patients with high-risk disease before progression [14].…”
Section: To the Editormentioning
confidence: 64%
“…Multiple myeloma (MM) is always preceded by an asymptomatic expansion of clonal plasma cells, clinically recognized as monoclonal gammopathy of undetermined significance (MGUS) or smoldering myeloma (SMM) 10,11,12 . Historically, translocations between the IGH locus and recurrent oncogenes and trisomies of odd chromosomes (i.e., hyperdiploidy) have been considered as initiating events 13,14 .…”
mentioning
confidence: 99%
“…Immunoparesis with suppression of uninvolved immunoglobulins is a well-recognized feature of multiple myeloma (MM) and has been associated with an inferior prognosis. For example, studies have linked immunoparesis with an increased risk of progression to MM from precursor states (1)(2)(3)(4)(5)(6). Similarly, several studies suggest immunoparesis in newly diagnosed patients is connected with a worse progression-free and overall survival (7,8), while immunoglobulin recovery after high-dose therapy confers a good prognosis (9,10).…”
Section: Introductionmentioning
confidence: 99%